Presynaptic Mitochondria Communicate With Release Sites for Spatio-Temporal Regulation of Exocytosis at the Motor Nerve Terminal - Lopez-Manzaneda, Mario; Fuentes-Moliz, Andrea; Tabares, Lucia (Frontiers in Synaptic Neuroscience, 2022)
Presynaptic Ca2+ regulation is critical for accurate neurotransmitter release, vesicle reloading of release sites, and plastic changes in response to electrical activity. One of the main players in the regulation of cytosolic Ca2+ in nerve terminals is mitochondria, which control the size and spread of the Ca2+ wave during sustained electrical activity. However, the role of mitochondria in Ca2+ signaling during high-frequency short bursts of action potentials (APs) is not well known. Here, we studied spatial and temporal relationships between mitochondrial Ca2+ (mCa2+) and exocytosis by live imaging and electrophysiology in adult motor nerve terminals of transgenic mice expressing synaptophysin-pHluorin (SypHy). Our results show that exocytosis hot spots and mitochondria are organized in subsynaptic functional regions that, together with the high sensitivity of mitochondria to uptake Ca2+, contribute to the regulation of the mode of fusion (synchronous and asynchronous) and the release and replenishment kinetics of the readily releasable pool (RRP) of vesicles. We propose that mitochondria modulate the timing and reliability of neurotransmission in motor nerve terminals during brief AP trains.